The Semantics-Pragmatics Interface: The Case Of The Singular Feminine Demonstrative in Jordanian Arabic - Jarbou, Samer Omar (Lesya Ukrainka Eastern European National University, 2017)
The aim in this study is to investigate the interface between semantics and pragmatics in relation to the use of the indexical demonstrative ‘haay’ ‘this-S.F.’ in Jordanian Arabic (JA)1 . It is argued here that an analysis of meaning in relation to context-sensitivity inherent in the use of ‘haay’ can give evidence to the view that semantic and pragmatic processes can be distinguished from each other. I have found that the meaning of ‘haay’ consists of three distinct levels: linguistic, semantic, and pragmatic meaning. The denotational and conventional senses of ‘haay’ comprise its linguistic meaning, its semantic meaning is generated when any of the variables in the linguistic meaning is selected in relation to ‘narrow context’, the pragmatic meaning depends on relating the semantic meaning to an entity in the physical context of interaction. The results of this study support the view that the boundary between semantics and pragmatics can be distinctively demarcated. Метою цього дослідження є вивчення взаємодії семантики та прагматики на прикладі використання вказівного займенника “haay” (“ця”) в йорданському варіанті арабської мови. У статті йдеться про те, що аналіз значення та його зв’язку з контекстною чутливістю, які притаманні використанню “haay”, може свідчити про те, що семантичні та прагматичні процеси можна розмежовувати. Автор стверджує, що значення “haay” складається з трьох чітких рівнів: мовного, семантичного та прагматичного. Денотативне та конвенціональне значення “haay” утворюють його лінгвістичне значення. Семантичне значення формується тоді, коли будь-яка змінна в лінгвістичному значенні вибирається у відношенні до “вузького контексту”, а прагматичне значення залежить від відношення семантичного значення до об’єкта у фізичному контексті взаємодії. Результати цього дослідження засвідчують думку про те, що семантика та прагматика можуть бути чітко розмежовані.
Keywords: semantics-pragmatics interface; deixis; demonstratives; Jordanian Arabic; кореляція семантики та прагматики; дейксис; вказівні займенники; йорданський варіант арабської мови